Transparency Overlays and Applications - Chase, Melissa; Meiklejohn, Sarah (CCS '16 Proceedings of the 2016 ACM SIGSAC Conference on Computer and Communications Security, 2016)
In this paper, we initiate a formal study of transparency, which in recent years has become an increasingly critical requirement for the systems in which people place trust. We present the abstract concept of a transparency overlay, which can be used in conjunction with any system to give it provable transparency guarantees, and then apply the overlay to two settings: Certificate Transparency and Bitcoin. In the latter setting, we show that the usage of our transparency overlay eliminates the need to engage in mining and allows users to store a single small value rather than the entire blockchain. Our transparency overlay is generically constructed from a signature scheme and a new primitive we call a dynamic list commitment, which in practice can be instantiated using a collision-resistant hash function.